Diurnal Asymmetric Loading Modulates Cell Phenotype in Intervertebral Disc - Ying Zhang; Jianbiao Xu; Zhiyu Zhou; R. Geoff Richards; Mauro Alini; Sibylle Grad; Zhen Li (JOR Spine, 2025)
ABSTRACT Purpose This study tested the hypothesis that asymmetric dynamic loading alone or in combination with static loading influences the morphological and biological characteristics of the intervertebral disc (IVD) cells in an ex vivo model. Methods Bovine caudal IVDs were assigned to four groups: (1) Parallel dynamic load (1 h) + free swelling (23 h); (2) Parallel dynamic load (1 h) + static load (23 h); (3) Wedge dynamic load (1 h) + free swelling (23 h); (4) Wedge dynamic load (1 h) + static load (23 h). IVD structure was assessed with measurements of height loss and histological staining. IVD tissue and cellular responses were also measured. Results Diurnal dynamic loading and free swelling recovery could maintain cell viability and the gene expression of organ‐cultured discs at their physiological level. Diurnal dynamic loading followed by static loading resulted in a degenerative condition, as indicated by lower cell viability, lower anabolic, and higher catabolic gene expression. Under the dynamic load + free swelling load regime, wedge loading upregulated the ACAN gene expression level in the concave and convex sides of the annulus fibrosus (AF) compared with day 0 healthy control. Under the dynamic load + static loading regime, the MMP1 gene expression showed a trend of increase in the concave and convex sides of the wedge group; the MMP13 gene expression showed a trend of increase in the concave side of the wedge group. The nucleus pulposus (NP) tissue in the wedge group showed a trend of protrusion toward the convex side. Conclusion Dynamic loading followed by continuous static loading negatively modulates the phenotype of IVD cells in this organ culture model. Comparable to the free swelling treatment after dynamic loading, physical treatment to reduce the stress on the IVD, even temporarily, may help to prevent the acceleration of deformity and degeneration. These results indicate that asymmetric loading followed by static loading may be used to mimic pathological changes of the IVD in spinal deformity.